Sociodemographic determinants of knowledge, attitude and practices of Ghanaian nurses towards persons living with HIV and AIDS in Kumasi - Dorothy Serwaa Boakye; Emmanuel Konadu; Azwihangwisi Helen Mavhandu-Mudzusi (Elsevier, 2023)
Introduction: Despite increasing knowledge, and awareness on HIV/AIDS, Countries and health institutions are still struggling to deal with the issues of stigma and discrimination towards patients living with HIV and AIDS amongst its staff. An investigation into other potential determinants/influences of nurses' knowledge, attitudes, and practices towards HIV/AIDS such as sociodemographic factors is therefore necessary Methods: The study used correlational cross- sectional design. A total of 247 participants from five selected health facilities were recruited through a simple random sampling. Chi-square analysis and Spearman's rank correlation were used to measure the level of association between the sociodemographic variables and knowledge, attitude and practices. Mean scores were calculated for knowledge, attitude and practices. Results: The study reported a significant correlation between nurses' knowledge and professional rank, year of work experience, in-service training, age, and their practice [(r = 0.216; p = 0.002), (r = 0.278; p = 0.0001), (r = 0.174; p = 0.010), (r = 0.173; r = 0.011), and (r = 0.176; p = 0.011)] respectively. Also, a significant correlation was observed between practice and age of the nurses (r = 0.151, p = 0.030). The attitude was positively associated with knowledge, professional rank, educational level, work experience, and age but negatively associated with practice and in-service training however there was no statistically significant correlation. Conclusion and recommendation: Nurses' knowledge, attitude and practice was directly correlated with their sociodemographic characteristics which suggests that policies and interventions aimed at improving nurses' knowledge, attitudes and practices should take into account their sociodemographic characteristics.